Intellectual property: Need& Importance - Yaseen Pasha (AG Volumes, 2021)
An intellectual property is a person's ability to express his or her thoughts and ideas in an original way. A person's intellectual property is an intangible asset, unlike physical property. The creators' exclusive rights to their works are known as "intellectual property rights," or "IPR." Common intellectual property rights include patents, copyrights, trademarks, industrial designs, trade secrets and integrated circuit layout design. IP rights encourage the creator to grow and share his or her work with others for the greater good of society. The primary goal of IPRs is to aid in the reduction of poverty, the stimulation of economic growth, the improvement of health status via the provision of medicines to the poor, the improvement of access to education and the contribution to overall sustainable development. Though intellectual property rights (IPRs) offer incentives for authors and inventors, they are also a type of intellectual protectionism or a temporary monopoly imposed by the state.